(untitled) - Grinnell, Scott (Australia, 2016)
This book evaluates different types of building materials and design options while assessing available forms of renewable energy--including solar, wind, hydro, biomass, tidal and geothermal. By examining the benefits and limitations involved in harnessing each of these renewable energies, this book seeks to provide you with an objective and informed viewpoint, with the ultimate purpose of minimizing harmful impacts on individuals, communities, and the environment.
Keywords: Tòa nhà bền vững,Sustainable buildings; Kết cấu và thiết kế,Design and construction